Beragam Indikator Pembangun Tingkat Kesadaran Lingkungan Petani Lahan Kering, Daerah Semi Arid, Timor Barat - Johanna Suek (Undana Press, 2019)
ABSTRACT Economic improvements are often found to neglect environmental sustainablity. Slash and burn systems and the application of inorganic materials that are thought to increase agricultural production, are instead causing land to be deforested and vulnerable to erosion.Humans has a direct dominance towards the majority of the ecosystem, meaning that humans has a large influence in affecting the quality of these ecosystems, wether the action of managing it improves or worsen the existing state of an ecosystem. Thus it is crucial to invite and guide the community to be aware of the facts and risks borne by the environment and the importance of actions to reduce these risks.Environmental awareness studies were conducted in eleven villages spreading across West Timor.The sampling technique was carried out by using the multistage quota random sampling method, and as many as 30 respondents were selected from each village, with data analysis done descriptively. Some findings in the study indicate that 46.67% of indicators that are considered as determinants of the environmental awareness level of farmers,shows a low index value ranging from 1.57 to 1.92.Furthermore, there are 33.33% of indicators that contribute enough with an index value smaller than 2.5.Only 20% of indicators contribute to the farmer awareness index at a sufficient level with an index value of>2.5, some of which are minimal use of inorganic fertilizers, periods of inorganic fertilizer use and minimal use of inorganic herbicides.Therefore, it is necessary to have synergistic actions from various components to improve the performance of the indicators that determine the environmental awareness of farmers. ABSTRAK Peningkatan ekonomi sering mengabaikan keberlanjutan lingkungan. Sistem tebas bakar dan aplikasi material anorganik diharapkan untuk meningkatkan produksi pertanian justru menyebabkan lahan menjadi bersih dari rerumputan dan pohon atau lahan menjadi gundul dan sangat rentan terhadap erosi. Manusia mendominasi secara langsung terhadap sebagian besar ekosistem. Artinya perilaku manusia sangat mempengaruhi kualitas suatu ekosistem, apakah pengelolaan yang dilakukan memperbaiki atau memperburuk kondisi eksisting ekosistem. Dengan demikian sangatlah krusial mengajak dan membimbing masyarakat menyadari fakta dan risiko yang ditanggung lingkungan dan pentingnya tindakan untuk mengurangi risiko tersebut. Studi kesadaran lingkungan dilakukan di sebelas desa yang menyebar di Timor Barat. Teknik pengambilan contoh dilakukan secara multistage quota random sampling, sebanyak 30 responden dari masing-masing desa. Analisis data dilakukan secara deskriptif. Beberapa temuan dalam studi menunjukkan bahwa terdapat 46,67% dari indikator yang dianggap sebagai penentu tingkat kesadaran lingkungan petani memiliki nilai indeks rendah, berkisar 1,57 sampai 1,92. Selanjutnya terdapat 33,33% indikator yang berkontribusi cukup dengan nilai indeks lebih kecil 2,5. Hanya sebesar 20% indikator yang berkontribusi terhadap indeks kesadaran petani pada tingkat yang cukup dengan nilai indeks >2,5, beberapa indikator tersebut adalah penggunaan minimal pupuk anorganik, periode penggunaan pupuk anorganik dan penggunaan minimal herbisida anorganik. Oleh karena itu perlu adanya tindakan sinergis dari berbagai komponen untuk meningkatkan performa dari indikator-indikator yang menentukan kesadaran lingkungan petani.